Railroad Transport Opportunity in Case of Consumer Goods - Bauer, Tomáš (2010)
The thesis covers topics related to railway transport of consumer goods. First, basic attributes of rail transport such as economic characteristics, history, development in time, infrastructure, and standards are presented. Second, major agents of rail transport and their functions are described. Third, international standards and rules applying to the railway transport are discussed, including the outcomes of EU initiatives as well as COTIF regulations. Fourth, a brief overview of consumer goods as an object of transport and further applications are presented. In the fifth part, a portfolio of quantitative instruments is described. Sixth, the final case study deals with application of the developed theoretical framework on a real business situation.